Influence of culture conditions on Vero cell propagation on non-porous microcarriers - Marta Cristina de Oliveira Souza; Marcos da Silva Freire; Leda dos Reis Castilho (Brazilian Archives of Biology and Technology, 2005)
Animal cell cultures are widely employed for the production of viral vaccines and for recombinant protein expression. The cell line Vero is a continuous, adherent cell line, which has been recommended by the World Health Organization for the production of human vaccines. For the large-scale production of vaccines, microcarriers, which are microspheres that serve as support for the cells, are being increasingly used. The use of microcarriers in stirred bioreactors allows high cell densities and, consequently, high virus titres to be achieved. With the aim of selecting appropriate culture conditions for the cultivation of Vero cells at high cell densities, in this work the influence of several variables (agitation rate, ratio of inoculated cells to microcarrier mass and fetal bovine serum concentration) on cell growth on Cytodex 1 microcarriers was studied. Under the best conditions determined, a comparison with Vero cell cultivation on Cytodex 3 microcarriers was carried out. Cultivos de células animais são amplamente utilizados para a produção de vacinas virais e para a expressão de proteínas recombinantes. A linhagem celular Vero é uma linhagem contínua, dependente de ancoragem, recomendada pela Organização Mundial de Saúde para a produção de vacinas de uso humano. Para a produção de vacinas virais em larga escala, vêm sendo cada vez mais empregados microcarregadores, que são microesferas que servem de suporte para as células. O emprego de microcarregadores em biorreatores agitados permite a obtenção de altas densidades celulares e, conseqüentemente, de altos títulos de antígenos virais. Com o objetivo de selecionar condições de cultivo adequadas, estudou-se, neste trabalho, o efeito das variáveis agitação, razão de células inoculadas por microcarregador e concentração de soro fetal bovino sobre o crescimento de células Vero em microcarregadores Cytodex 1. Nas melhores condições selecionadas, o desempenho dos microcarregadores Cytodex 1 e Cytodex 3 foi comparado.